Anmeldelser - Fjeldsøe, Michael (Danish Yearbook of Musicology, 2011)
Review of: Anne-Marie Reynolds: Carl Nielsen’s Voice. His Songs in Context. Danish Humanist Texts and Studies, 38. Copenhagen: Museum Tusculanum Press / The Royal Library, 2010. Daniel M. Grimley: Carl Nielsen and the Idea of Modernism. Woodbridge: The Boydell Press, 2010.